Motivation Analysis of Technological Startups Business Models Based on Intelligent Data Mining and Analysis - Xuejiao Ren; Xiaozhou Ding (Journal of Electrical and Computer Engineering)
To improve the motivation analysis effect of the technological startups business model, this study combines intelligent data mining technology to analyze related factors and proposes a method of adjusting parameters of machine-learning model based on Bayesian optimization algorithm. Moreover, this study integrates the prior information and sample information of the machine learning algorithm performance function and builds an intelligent analysis model based on the elements of the technological startups business model. Finally, this article designs experiments to evaluate the effect of intelligent data mining of the system model in this study. The research shows that the motivation analysis model of the technological startups’ business model based on intelligent data mining analysis proposed in this study meets the basic requirements of the design system of this study.